PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA SEKOLAH DASAR (Studi Eksperimen Kelas V SD Negeri 163 Pekanbaru - Siregar, Sylvia Fransiska Siregar Fransiska; Kurniaman, Otang Kurniaman Otang; Noviana, Eddy Noviana Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT: This research carried out base on the low learning outcomes IPS that the average value of class 64.10. While the value of a minimum completeness criteria (KKM) IPS is 72. This is due to saturation of students receiving social studies in school. Teachers simply use the ordinary learning that teachers in presenting the material without any new model of learning, discussion and assignment, making it less encourage students to study seriously, it causes students less interested in social studies. This research was a pure experiment that aimed to find out the difference between the results of social studies classroom experiments by applying cooperative learning model talking stick and control class by implementing regular teaching fifth grade students of SDN 163 Pekanbaru. Quantitative data collection techniques such as the value of the initial test (pretest) and final test (posttest). This thesis presents the study results of initial tests scores (pretest) prior to the action on the control class VD 40.10 increased to 60.35 at the end of the test scores of learning outcomes (posttest), while scores of initial tests of learning outcomes (pretest) prior to the action in the experimental class VB 49.23 increased to 63.35. Increase students' understanding of the criteria obtained lower scores on the index gain 0.27 experimental class by applying the model talking stick and criterion scores low on the index gain control grade 0.26 by applying the usual learning. T-test gain indices prove - t table ≤ t ≤ + t table or -1.992 <0.04 <1.992, obtained is Ho accepted and Ha rejected. The results of social studies students of class V SDN 163 Pekanbaru acquire learning by using cooperative learning model talking stick increased learning outcomes, but does not have a significant difference to the learning outcomes of students who received the usual application of learning.Keywords: Model Talking Stick, IPS Learning Outcomes2